Exercise Dysfunction and Pulmonary Rehabilitation Strategies in COPD Patients at High-Altitudes: A Review - Fan LX; Wang HJ (International Journal of COPD)
Lin-Xia Fan, Hong-Juan Wang Department of Respiratory Medicine, Gansu Provincial Hospital, Lanzhou, Gansu, 730000, People’s Republic of ChinaCorrespondence: Hong-Juan Wang, Department of Respiratory Medicine, Gansu Provincial Hospital, Lanzhou, Gansu, 730000, People’s Republic of China, Tel +86 15117046868, Email coldrain_591@163.comAbstract: Chronic Obstructive Pulmonary Disease (COPD) presents significant challenges for patients at high-altitudes, where reduced oxygen availability exacerbates exercise dysfunction. This review explores the related factors behind exercise limitations in high-altitude COPD patients, including chronic hypoxia, impaired pulmonary function, cardiovascular responses, muscle dysfunction, and psychological factors. Effective pulmonary rehabilitation (PR) strategies are essential and should encompass individualized assessments, tailored exercise programs, supplemental oxygen therapy, and nutritional and psychological support. This review highlights the need for further research to develop specific PR protocols for high-altitude COPD patients, focusing on long-term outcomes and innovative approaches to improve access to rehabilitation services. By addressing both physiological and psychological aspects, these strategies aim to enhance the quality of life and functional capacity of COPD patients in high-altitude environments.Keywords: chronic obstructive pulmonary disease, COPD, high-altitude, exercise dysfunction, pulmonary rehabilitation, hypoxia